Eksistensi dan Revitalisasi Pesantren di Era 4.0 - Rindiani, Ani; Nurwadjah, Ahmad; Suhartini, Andewi (Ikatan Da'i Indonesia, 2022)
Pesantren is the oldest traditional Islamic educational institution in Indonesia. The rapid development of the current of globalization requires pesantren to make changes and developments in order to maintain their existence in society. This study aims to examine the revitalization of the existence of Islamic boarding schools in the 4.0 era by using the library research method, namely research conducted through data collection that is library in nature. The results of this study indicate that the existence of Islamic boarding schools still exists in the midst of globalization, which can be seen from several indicators, namely (1) Moral values ​​remain the guide and reference in all activities and become the main point of the education system developed in it. (2) as a functional educational institution, Islamic boarding schools are able to provide answers to various problems faced by the community. (3) the pesantren education system is quite anticipatory to the needs of the community, (4) Islamic boarding schools always modernize their education system by not only teaching religious sciences, but also teaching general subjects in the national education system. (5) modern pesantren education does not exclude technology education. (6) Islamic boarding school students are given lessons to solve problems in elegant and civilized ways. Efforts that can be developed in an effort to revitalize the existence of Islamic boarding schools include building digital literacy in Islamic boarding schools, and creating channels for Islamic studies.